Feminism-in-Action: Dr. Diana Scully - Canfield, Liz (Violence against women, 2023)
This essay is a tribute to the former founding Department Chair of Women's Studies at Virginia Commonwealth University, Dr. Diana Scully, by Liz Canfield, a current Associate Chair of the same department.